Auditory Attention Decoding – Constructing a Study – (Student Conference Proceedings, 2025)
Globally rising life expectations lead to increasing age-related conditions which need to be addressed by modern medicine. One of these is age-related hearing loss and the subsequent use of hearing aids (HA). A problem commonly associated with HA is the "cocktail party problem" occurring during social gatherings and potentially making the person with impaired hearing unable to focus on their chosen speaker due to too much background noise. To improve the living conditions of hearing impaired people, a study was planned using Auditory Attention Decoding (AAD) to understand the processing of directional hearing in the brain during a listening task with different speakers and distracting noises. Out of three initial concepts, one idea was transformed into a program. AAD provided a possibility for the development of a study and its technical preparation. The results are intended to provide insight into the processing of incoming audio signals performed by the human brain.
Keywords: Auditory Attention Decoding; Listening Task; Hearing Aids